COMMUNICATING DEMOCRATIC WILL ONLINE: THE CASE OF MASS REJECTION TO FUEL PRICE ADJUSTMENT POLICY IN INDONESIA - Wahyu Nova Riski (Jurnal Ranah Komunikasi, 2023)
The advance of communication technologies has evolved civic engagement in democratic countries. Social media platforms such as Twitter, Facebook, and Instagram allow citizen to express their view freely and publicly. Citizens can easily communicate their views about the democratic process through social media. This study aims to assess online democratic engagement on Twitter in Indonesia regarding the policy to increase fuel prices in 2022. Computerized social network analysis is employed. NodeXL Pro is an open-source web scraping and visualization tool used to collect, process, and analyze Twitter data. The study finds that online civic engagement tends to be polarised in the network structure. Secondly, this study indicates that general public are important figure in the network. Meanwhile, the primary source of information discussed in the network is news media. Finally, this study demonstrates a link between online political discourse and traditional media coverage.